1979
DOI: 10.1002/dev.420120305
|View full text |Cite
|
Sign up to set email alerts
|

Development of the acoustic startle response in the rat: Ontogenetic changes in the magnitude of inhibition by prepulse stimulation

Abstract: Three experiments examined the development of the acoustic startle reflex and its modification by a preliminary stimulus in the infant rat during the 2nd and 3rd postnatal weeks. The 1st experiment employed a white noise S1 (20 msec, 70 dB), the 2nd a cutaneous S1 (.5 msec, .5 mA and 1.0 mA shock), and the 3rd identical S1-S2 pairs (20 msec, 10 kHz, 110 dB tones). The results demonstrate a similar maturation of the prepulse modification pattern over days in the 3 experiments, evidenced mainly in the growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 27 publications
5
49
1
Order By: Relevance
“…First, the effective interstimulus interval for inhibition in fish is comparable with previously reported effective lead intervals in humans (Braff et al, 1978), rats (Parisi and Ison, 1979;Mansbach and Geyer, 1991), and primates (Javitt and Lindsley, 2001). Second, as in higher vertebrates, prepulse inhibition in fish is modulated by dopaminergic and glutamatergic drugs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…First, the effective interstimulus interval for inhibition in fish is comparable with previously reported effective lead intervals in humans (Braff et al, 1978), rats (Parisi and Ison, 1979;Mansbach and Geyer, 1991), and primates (Javitt and Lindsley, 2001). Second, as in higher vertebrates, prepulse inhibition in fish is modulated by dopaminergic and glutamatergic drugs.…”
Section: Discussionsupporting
confidence: 80%
“…As in rats, where PPI can be demonstrated at the onset of auditory acuity (Parisi and Ison, 1979), we could elicit inhibition in larvae as young as 3 dpf, when occasional acoustic startle responses can first be elicited (data not shown). We found robust PPI across a range of developmental stages, persisting into adulthood.…”
Section: Prepulse Inhibition Of Slc Startle Responsesmentioning
confidence: 73%
“…Our previous work showed that term infants <4 days of age failed to show reflex inhibition to acoustic stimuli even at an IS1 of 600 ms 1985). A clear ontogenetic event with regard to reflex inhibition is revealed in the neonatal rat pup (Parisi and Ison, 1979). The ability to inhibit to an acoustically elicited startle reaction by either an auditory or tactile stimulus was initially weak but progressed during the second and third weeks following birth, with tactile stimuli providing reliable inhibition at an earlier age than acoustic stimuli.…”
Section: Discussionmentioning
confidence: 94%
“…Although it appears in the figure that the 17-day-olds had larger absolute response levels, recall that the sensitivity of the transducer platform was recalibrated for each age. In fact, absolute startle-response amplitudes increase across this age range (Hunt et al, 1994;Parisi & Ison, 1979).…”
Section: Resultsmentioning
confidence: 94%
“…Prepulse inhibition of startle is a form of reflex modulation that is evident in the 17-day-old rat (Parisi & Ison, 1979 with auditory and visual prepulses. Thus, the circuitry underlying unconditioned inhibition of startle by visual prepulses is present by Day 17, while the circuitry underlying fear potentiation of startle using visual CSs is not fully mature until several days later.…”
Section: Discussionmentioning
confidence: 99%